IP-10 Interferes With the Antiviral Response of Direct-Acting Antiviral Agents for Hepatitis C Virus Infection - Wang, Yadong; Hu, Yangyang; Zhang, Xing; Luo, Yue; Ma, Luyuan; Lu, Jingjing; Liang, Qianfei; Xu, Chengjun; Zhao, Caiyan; Pan, Calvin Q. (Frontiers in Public Health, 2022)
Background: Increased Interferon (IFN)-gamma-inducible protein-10 (IP-10) level has been shown associated with sustained virologic responses (SVR) to pegylated interferon-alpha 2a/ribavirin-based therapy in chronic hepatitis C (CHC) patients. We investigated the relationship between IP-10 and treatment response in CHC patients treated with direct-acting antiviral agents (DAAs) therapy. Methods: We measured the dynamic changes of IP-10 in samples from 90 CHC patients. The serum IP-10 levels, intrahepatic expressions of IP-10 mRNA, and protein were determined respectively. For the in vitro experiments, the expression changes of IP-10 in hepatitis C virus (HCV)-replicating Huh-7 cells with or without nonstructural protein 5A (NS5A) inhibitor were analyzed by real-time reverse transcription-polymerase chain reaction and western blotting. Results: CHC patients had increased baseline IP-10 levels, intrahepatic IP-10 mRNA, and protein expression. After initiating DAAs therapy, serum IP-10 levels decreased gradually in patients who achieved cure, whereas, in patients who failed the therapy, IP-10 levels did not change significantly or rebound from the initial decline. Multivariate logistic regression analysis confirmed that baseline IP-10 level≤450 pg/mL and decline >30% at 12 weeks independently predicted the SVR in CHC patients who received DAAs. In vitro study, the expression of IP-10 mRNA and protein in HCV-replicating Huh-7 cells increased significantly. However, such activities were downregulated by NS5A inhibitor, followed by the reduction of HCV RNA levels and IP-10 levels decline. Conclusions: IP-10 interfered with HCV replication in hepatocytes and the dynamic decline in IP-10 levels during DAA treatment predicted the SVR in CHC patients.